2018
DOI: 10.1088/1742-5468/aae028
|View full text |Cite
|
Sign up to set email alerts
|

Time-inhomogeneous random Markov chains

Abstract: We consider Markov chains with random transition probabilities which, moreover, fluctuate randomly with time. We describe such a system by a product of stochastic matrices, U (t) = Mt · · · M1, with the factors Mi drawn independently from an ensemble of random Markov matrices, whose columns are independent Dirichlet random variables. The statistical properties of the columns of U (t), its largest eigenvalue and its spectrum are obtained exactly for N = 2 and numerically investigated for general N . For large t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It is shown that the singular values and eigenvalues of √ nP follow the appropriate universal laws. Different models for random transition matrices have been considered in [12,13,15,19,20,24,41,42,46,54,56,79].…”
Section: Random Transition Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that the singular values and eigenvalues of √ nP follow the appropriate universal laws. Different models for random transition matrices have been considered in [12,13,15,19,20,24,41,42,46,54,56,79].…”
Section: Random Transition Matricesmentioning
confidence: 99%
“…Viewing i as a cycle on G i we let r 1 (i) be the number of edges which are traversed exactly once Figure 5. Visualization of a sequence of integers i for which P (i) has an asymptotically relevant contribution to (42). The corresponding undirected graph G i is the tree found by identifying the doubled edges.…”
Section: Numerical Experiments On Manhattan Taxi Tripsmentioning
confidence: 99%
“…Statistics of the real eigenvalues in particular have been shown to arise in many diverse areas, notably in connection to annihilating Brownian motions [43,42,37,16], random dynamical systems [23] and recently to an inverse scattering solution of the Zakharov-Shabat system [6]. Real eigenvalues of products have been applied to physical problems [31,26] and recently appeared in connection to random Markov matrices [27]. The analogue of the results discussed above for products of complex matrices also hold here: products of independent real Ginibre matrices are again described by a Pfaffian point process [28,18].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Statistics of the real eigenvalues have been shown to arise in many diverse areas, notably in connection to annihilating Brownian motions [41,40,35,15], random dynamical systems [22] and recently to an inverse scattering solution of the Zakharov-Shabat system [6]. Real eigenvalues of products have been applied to physical problems [30,25] and recently appeared in connection to random Markov matrices [26]. The analogue of the results discussed above for products of complex matrices also hold here: products of independent real Ginibre matrices are again described by a Pfaffian point process [27,17].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%